Tropical cyclones enhance photosynthesis in moisture-stressed regions of India - Rahul Kashyap; Jayanarayanan Kuttippurath (npj Climate and Atmospheric Science)
Abstract We unravel the response of terrestrial ecosystems in India to Tropical Cyclones (TCs) originating in the North Indian Ocean (NIO). We find that about 34.6% of TCs drove greening and 65.4% caused browning response of vegetation during 2000–2020. TC-induced greening is more likely for TCs originated in pre-monsoon (100%) or monsoon (62.5%) than post-monsoon with large browning response (94%). Rainfall by TCs increases soil moisture (SM) and reduces climatic water deficit (CWD) for a moisture-stressed region, and its effective utilisation by vegetation triggers the greening response. Granger Causality reveals that TC-induced rain and greening response exhibit a maximum temporal lag of 40 days. The favourable vegetation response to TCs is a new insight as it sheds light on the complex Atmosphere-Land-Ocean (ALO) interactions on a regional scale. The findings can aid to improve climate models for better policy decisions aimed at climate adaptation and sustainability on both regional and global scales.